2020
DOI: 10.1183/13993003.02255-2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the latent tuberculosis screening and treatment strategy for asylum seekers in Stockholm, Sweden 2015–2018: a record linkage study of the care cascade

Abstract: In many countries with low tuberculosis (TB) incidence (<10/100,000) a high proportion of cases originate from latent TB infection (LTBI) reactivation among migrants from high-incidence countries (≥100/100,000) who have been infected before arrival in the host country [1, 2]. Consequently, LTBI screening and management for migrants is an important intervention to reduce TB incidence in those countries [1, 3, 4].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Cost-effectiveness of LTBI screening is dependent on patient and provider adherence [ 16 ]. We have previously shown that the present screening strategy is implemented largely according to policy and that patient adherence is high [ 15 ]. Still, this screening strategy is only clearly cost-effective for some subgroups, while it is not cost-effective for others.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Cost-effectiveness of LTBI screening is dependent on patient and provider adherence [ 16 ]. We have previously shown that the present screening strategy is implemented largely according to policy and that patient adherence is high [ 15 ]. Still, this screening strategy is only clearly cost-effective for some subgroups, while it is not cost-effective for others.…”
Section: Discussionmentioning
confidence: 99%
“…The restrictive policy for LTBI treatment for the age group 20–34 in Stockholm has been questioned and might be seen as conservative compared to other regions of Sweden where treatment is recommended for those up to the age of 35 [ 15 , 29 ] In addition, the cascade of care data collected in this cohort shows high rates of treatment completion rates [ 15 ] which is promising for the effectiveness and cost-effectiveness of LTBI screening. A recent review concluded that effectiveness of LTBI programs in the EU/EEU is largely limited by a weak care cascade when a minority of migrants who are screened complete preventive treatment [ 30 ], which seems not to be a problem in the Stockholm setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations